Марківські моделі процесів ліквідації аварій в людино-машинних системах - Разі, Д. Ш. (My University, 2014)
Процес ліквідації аварії у всіх моделях відбувається в кілька етапів, з різними інтенсивностями і можливими багаторазовими повтореннями етапів у випадку «мультикатастроф». Запропоновано марківську модель, в якій ймовірності зміни станів здоров'я оператора в ході ліквідації аварії знайдені за допомогою принципу максимізації інформаційної ентропії. Оцінено час стабілізації процесу і адекватність заміни динамічної моделі на стаціонарну. Введено та досліджено критерій безпеки ситуації, як відношення середнього періоду між аваріями до середнього часу відновлення. The “Man-machine-environment” system is considered. It has either classic flow of events, or a flow of unstable of natural disasters with different densities, that are approximated by piecewise constant functions. The process of liquidation of the accident in all the models is held in several stages, with different intensities. The phases can be made repeatedly in the case of "multi-catastrophes". The Markovian model is presented, in which the probability of changes in health of the operator in the process of liquidation of the accident is found using the principle of maximizing the information entropy. The stability time of the process and the value of changing the dynamic model to stationary one are estimated. The safety criterion of situation that is the ratio of the average time between failures and mean time of recovery is introduced and investigated.
Keywords: людино-машинна система; відновлення працездатності; ланцюг Маркова; рівняння Колмогорова; максимальна ентропія; Human-Machine System; Recovery; Markov chain; Kolmogorov equations; Maximum entropy